Computational investigation of blood flow in fusiform models of aortic aneurysms: a steady state analysis. (2015) - Vinoth, R.; Kumar, D.; Adhikari, Raviraj; Devaprasad, Dedeepiya; Kaliyamoorthy, Dhamodharan
Laminar, turbulent and transitional numerical simulations of steady flow in an aneurysmal aorta with different aneurysm diameters were carried out using Computational Fluid Dynamic (CFD) technique. The simulation of steady flow condition in normal aorta was also carried out to provide the data for comparison with an aneurysmal aorta data. Results were calculated for Wall Shear Stress (WSS) patterns, pressure and velocity fields from normal aorta and aneurysmal aorta models. The pressure drop values were also calculated analytically for each model to compare with numerically simulated one. The larger aneurysm models demonstrated unstable flow with greater magnitude of instability at the distal portion of aneurysm, the flow in the smaller models became stable. The results of pressure drop value show that the laminar fluid flow model is desirable for normal aorta and smaller aneurysm models, the transitional flow model is suitable for larger aneurysm models.